Adiponectin Receptors Are Less Sensitive to Stress in a Transgenic Mouse Model of Alzheimer's Disease - Várhelyi, Zoltán P.; Kálmán, János; Oláh, Zita; Ivitz, Eszter V.; Fodor, Eszter K.; Sántha, Miklós; Datki, Zsolt L.; Pákáski, Magdolna (Frontiers in Neuroscience, 2017)
Background: Adiponectin and leptin are implicated in the initiation and pathomechanism of Alzheimer’s disease (AD). The serum concentrations of these adipokines has been extensively studied in AD, however little is known about their receptors in this disease. Objective: We developed a novel approach to examine whether the receptors of adiponectin (AdipoR1 and -R2) and/or leptin (LepR) can contribute to AD pathomechanism. To achieve this, we investigated the effect of both genetic and environmental factors associated with AD on the expression of these receptors. Method: We used C57BL/6J (WT) and APP(swe)/Presen(e9d)1 (AD) mice. Both strains were exposed to restraint stress (RS) daily for 6h over different time periods. Then, we measured the mRNA expression of AdipoR1, AdipoR2 and LepR and the level of AdipoR1 and AdipoR2 proteins in the hippocampal and prefrontal cortical areas of each mouse. Results: We detected brain region specific transcriptomic changes of adiponectin receptors induced by APP and PS1 transgenes. Both acute and chronic RS caused significant elevations in AdipoR1 mRNA expression in the hippocampus of WT mice. In the prefrontal cortex, the mRNA expression of AdipoR1 followed a biphasic course. In AD mice, RS did not promote any changes in the expression of AdipoR1 mRNA and AdipoR1 protein levels. AdipoR2 mRNA in AD animals, however, showed a significant increase in the prefrontal cortex during RS. Regarding AdipoR1 and AdipoR2 mRNA and protein expression, relevant changes could be measured during stress exposure in both brain areas. Furthermore, stress exposed groups exhibited little change in LepR mRNA expression. Conclusion: Our findings indicate that carrying the transgenes associated with AD induces modification in the expression of both adiponectin receptors. In the case of a normal genetic background, these receptors also appear to be sensitive to environmental factors, while in a genetically determined AD model less response to stress stimuli could be observed. The results suggest that modification of adipokine receptors could also be considered in the therapeutic approach to AD.